Tacrolimus immunosuppression in high-risk corneal grafts. Issue 1 (6th September 2006) - Joseph, A; Raj, D; Shanmuganathan, V; Powell, R J; Dua, H S
Abstract : Background: Unlike the immune privilege enjoyed by low-risk corneal grafts, high-risk corneal grafts experience rejection rates comparable to liver and kidney transplants. Systemic immunosuppression reduces the risk of rejection in high-risk corneal grafts. Methods: Systemic tacrolimus, a specific T cell inhibitor, was used at a mean daily dose of 2.5 mg to immunosuppress 43 patients undergoing high-risk corneal transplantation. Immunosuppression was continued for a period of 18–24 months after the high-risk corneal graft. Results: During a mean follow-up period of 33.7 months, clarity of the graft was maintained in 65% of patients. Eight patients experienced rejection episodes while on tacrolimus, and this led to graft failure in five patients. Conclusion: Tacrolimus is relatively safe and effective in reducing rejection and prolonging graft survival in patients with high-risk keratoplasty compared with other series where similar immunosuppression was not used.